The capsular group B meningococcal vaccine, 4CMenB : clinical experience and potential efficacy. - Rollier, C; Dold, C; Marsay, L; Sadarangani, M; Pollard, A (Taylor and Francis, 2014)
INTRODUCTION: Capsular group B meningococcal disease is a leading cause of childhood meningitis and septicaemia. Up to 10% of sufferers die, and sequelae remain in > 30% of survivors. A vaccine, four component meningococcal group B ( 4CMenB ), designed with the aim to induce broad coverage against this highly variable bacterium, has been licensed in countries including in the European Union, Canada and Australia. AREAS COVERED: Immunogenicity and safety data, published in peer-reviewed literature between 2004 and 2014, are presented in the context of the recent recommendation for the use of the vaccine in infants in the UK. EXPERT OPINION: 4CMenB induces significant reactogenicity when administered with routine infant vaccines, in particular with respect to fever rates. Fevers can be somewhat reduced using paracetamol. The efficacy of the vaccine is unknown but has been extrapolated from effectiveness data obtained from use of one of its components in New Zealand, immunogenicity data from clinical trials and estimation of coverage from in vitro studies. These data suggest that the vaccine will prevent a proportion of invasive meningococcal disease cases in infants and young children. Implementation and well-planned post-marketing surveillance will address uncertainties over field effectiveness.